Usage of E-Resources by the PG Students of Doaba College Jalandhar:A Case Study - Singh, Jagjit (Journal of Information and Knowledge, 2016)
Students are the backbone of any institution and success of any institution especially library depends upon the use of library resources. Post Graduate students use e-resources for their study, research and for consultancy purposed. Libraries have been playing very active role in providing adequate opportunities for the use of electronic resources to their users. The present study concerns with the usage of electronic resources by the PG students of Doaba College Jalandhar. The study focuses on the role of e-resources in their study, research orientation, level of satisfaction, quality of search, number of e-resources, accessibility, services, training and assistance provided by library for the use of e-resources.